Efektivitas Susu Kambing Etawa sebagai Terapi Pendukung dalam Penanganan Tuberkulosis - Dina, Farha (Maliki Interdisciplinary Journal, 2025)
Tuberculosis (TB) remains a global health issue, and effective treatment requires a multidisciplinary approach, including adequate nutrition. Etawa goat milk, rich in protein, medium-chain fatty acids, zinc, and selenium, holds potential in supporting the recovery of TB patients. This study aims to explore the benefits of Etawa goat milk in improving nutritional status and enhancing the immune system of TB sufferers. Etawa goat milk is known to aid in tissue repair, reduce inflammation, and boost immune response through its essential nutrients. Although Etawa goat milk shows potential as an adjunct therapy in TB treatment, stronger clinical evidence is needed to confirm its effectiveness. Further research with clinical trials is required to determine the optimal dosage and administration method.